Interocular Transfer: The Dichoptic Flash-Lag Effect in Controls and Amblyopes - Wang, Xi; Song, Yutong; Liao, Meng; Hess, Robert F.; Liu, Longqian; Reynaud, Alexandre (Investigative ophthalmology & visual science, 2022)
The mammalian brain can take into account the neural delays in visual information transmission from the retina to the cortex when accurately localizing the instantaneous position of moving objects by motion extrapolation. In this study, we wanted to investigate whether such extrapolation mechanism operates in a comparable fashion between the eyes in normally sighted and amblyopic observers.PurposeThe mammalian brain can take into account the neural delays in visual information transmission from the retina to the cortex when accurately localizing the instantaneous position of moving objects by motion extrapolation. In this study, we wanted to investigate whether such extrapolation mechanism operates in a comparable fashion between the eyes in normally sighted and amblyopic observers.To measure interocular extrapolation, we adapted a dichoptic version of the flash-lag effect (FLE) paradigm, in which a flashed bar is perceived to lag behind a moving bar when their two positions are physically aligned. Twelve adult subjects with amblyopia and 12 healthy controls participated in the experiment. We measured the FLE magnitude of the subjects under binocular, monocular, and dichoptic conditions.MethodsTo measure interocular extrapolation, we adapted a dichoptic version of the flash-lag effect (FLE) paradigm, in which a flashed bar is perceived to lag behind a moving bar when their two positions are physically aligned. Twelve adult subjects with amblyopia and 12 healthy controls participated in the experiment. We measured the FLE magnitude of the subjects under binocular, monocular, and dichoptic conditions.In controls, the FLE magnitude of binocular condition was significantly smaller than that of monocular conditions (P ≤ 0.023), but there was no difference between monocular and dichoptic conditions. Subject with amblyopia exhibited a smaller FLE magnitude in the dichoptic condition when the moving bar was presented to the amblyopic eye and the flash to the fellow eye (DA condition) compared to the opposite way around (DF condition), consistent with a delay in the processing of the amblyopic eye (P = 0.041).ResultsIn controls, the FLE magnitude of binocular condition was significantly smaller than that of monocular conditions (P ≤ 0.023), but there was no difference between monocular and dichoptic conditions. Subject with amblyopia exhibited a smaller FLE magnitude in the dichoptic condition when the moving bar was presented to the amblyopic eye and the flash to the fellow eye (DA condition) compared to the opposite way around (DF condition), consistent with a delay in the processing of the amblyopic eye (P = 0.041).Our observations confirm that trajectory extrapolation mechanisms transfer between the eyes of normal observers. However, such transfer may be impaired in amblyopia. The smaller FLE magnitude in DA compared to DF in patients with amblyopia could be due to an interocular delay in the amblyopic visual system. The observation that normal controls present a smaller FLE in binocular conditions raises the question whether a larger FLE is or is not an indicator of better motion processing and extrapolation.ConclusionsOur observations confirm that trajectory extrapolation mechanisms transfer between the eyes of normal observers. However, such transfer may be impaired in amblyopia. The smaller FLE magnitude in DA compared to DF in patients with amblyopia could be due to an interocular delay in the amblyopic visual system. The observation that normal controls present a smaller FLE in binocular conditions raises the question whether a larger FLE is or is not an indicator of better motion processing and extrapolation.